2018
DOI: 10.1111/epp.12460
|View full text |Cite
|
Sign up to set email alerts
|

First records of Scaphoideus titanus (Hemiptera, Cicadellidae) in Ukraine

Abstract: The invasive leafhopper Scaphoideus titanus (Hemiptera, Auchenorrhyncha, Cicadellidae) is an important pest of vineyards in Europe as a vector of ‘Candidatus Phytoplasma vitis’, the causal agent of flavescence dorée, which is on the EPPO A2 List of pests recommended for regulation. Scaphoideus titanus has been recorded from the territory of Ukraine for the first time. Specimens were found in 2017 in the Transcarpathian Region (Zakarpattia Oblast).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As average temperatures increase during the growing season, S. titanus is expanding its range northward [ 191 ]. While short summers are considered a barrier to the northern spread of S. titanus due to the insect’s inability to reach its full life cycle [ 192 , 193 ], climate change with longer and hotter summers should favour the spread of S. titanus in northern vineyards such as in Germany by extending the favourable development period [ 191 ]. Currently, S. titanus is widely spread in many vine growing areas across the Europe.…”
Section: Climate Under Changementioning
confidence: 99%
See 1 more Smart Citation
“…As average temperatures increase during the growing season, S. titanus is expanding its range northward [ 191 ]. While short summers are considered a barrier to the northern spread of S. titanus due to the insect’s inability to reach its full life cycle [ 192 , 193 ], climate change with longer and hotter summers should favour the spread of S. titanus in northern vineyards such as in Germany by extending the favourable development period [ 191 ]. Currently, S. titanus is widely spread in many vine growing areas across the Europe.…”
Section: Climate Under Changementioning
confidence: 99%
“…Currently, S. titanus is widely spread in many vine growing areas across the Europe. Mirutenko et al [ 193 ] reported the occurrence of S. titanus in Ukraine, which is currently its northern limit of distribution in Europe. However, climate warming at the southern limit of its current range could lead to insect declines or extinctions of small populations in areas such as southern Italy [ 192 ].…”
Section: Climate Under Changementioning
confidence: 99%
“…However, with climate change and the consequent increase in average temperatures, S. titanus is expected to expand its range in northern vineyards (e.g. in Germany) and increase the risk of introduction of flavescence dorée into these regions (Boudon‐Padieu, 2007; Mirutenko et al., 2018).…”
Section: Climate Change Impact On Pest Distributionmentioning
confidence: 99%